Multifocal circumscribed choroidal hemangioma: a rare occurrence. Issue 2 (5th February 2020) - Vempuluru, Vijitha S; Kaliki, Swathi
Abstract : A 32-year-old Asian-Indian woman presented with painless diminution of vision in her left eye (oculus sinister (OS)) and fundus examination OS revealed a large dome-shaped orangish-red subretinal lesion at the macula along with a smaller lesion on the superotemporal arcade. Indocyanine green angiography and optical coherence tomography features confirmed the diagnosis of multifocal circumscribed choroidal hemangioma (CCH). There was no evidence of Sturge-Weber syndrome. CCH is usually solitary with only one reported case of multifocal CCH in the literature.